Desafios e possibilidades da política de formação de professores e professoras do campo: a experiência da Licenciatura em Educação do Campo da UFMA - LOPES, Safira Rego (2022)
The present work has as object of study the Degree in Field Education at the Federal University of Maranhão (UFMA). Its goal is to analyze the process of implementation of the course having as a parameter the educational principles listed in its Political-Pedagogical Project, which are based on the concept of field education elaborated from the field education movement. To this end, the investigation is guided by the dialectical historical materialism, which allows us to analyze this policy as part of a dialectical and contradictory totality, seeking to understand it in the context of a class society. The methodological procedures used were documentary research and semi-structured interviews with teachers and the articulating team of the course at the University. The data analysis was performed using the content analysis technique, referenced by Bardin (1977). The policy to train field educators is part of a counter-hegemonic project and is built from the dynamics of the class struggle that is inserted in the capitalist State, taking advantage of its fissures and contradictions. To understand this dynamic between State and civil society that crosses the composition of field education policies, we refer mainly to the works of Poulantzas (2015) and Gramsci (2020). As for the history and the foundations of field education, as well as for the analysis of the struggles for the formation of field educators, we resorted to authors such as Caldart (2003, 2004, 2008, 2010, 2011), Molina (2010, 2012, 2015, 2017), Molina and Antunes-Rocha (2014), Santos (2012), among others. On the configuration of public policies we used Arretche (2001) and Draibe (2001). In our empirical research, we took as a basis the Political Pedagogical Project of the Degree in Field Education of the Federal University of Maranhão (2014a, 2014b) from which we extracted the guiding principles of the analysis of its implementation. This project is based on a conception of field education originated in the struggles of peasant movements and defends a society that overcomes the division of classes, social inequalities, and the dichotomies between countryside and city, and especially the educational dichotomies, where there is a separation between intellectual and technical training, having labor as the educational principle. The results indicate that the Degree in Field Education at UFMA faces several tensions in order to consolidate itself in the university space as a course whose training points to a new human and societal referential, where the field is freed from the different fences that cross it: whether those of the latifundium or those of knowledge. Tensions that range from the moment of implementation with confrontations between the course management and the administrative structure of UFMA and that also go through internally divergent conceptions about the meaning of the formation of rural educators.